Application of Learning Management Functions in Realizing the Goals of the Bandung Islamic Institution - Imraan, Mohd; Rohaeni, Anie (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
The aim of the research is to determine the application of management functions in realizing institutional goals. Inhibiting factors and solutions. The research method uses a descriptive qualitative approach, describing events in the research field. Data collection techniques through field observations and observations in the environment. Conduct in-depth interviews with key respondents. Carrying out documentation studies through existing archives. Researcher intervention through data reduction, data presentation, data verification and triangulation. The results of the research show that the management function of the school principal is running in accordance with the goals planned by the school principal. Implementation in the field shows that in its implementation there are indications of irregularities. The learning process is ongoing at school. In essence, the school principal has implemented management functions, but has not been effective overall. Researchers suggest that students avoid violating rules and regulations. The school principal should improve the management functions of planning, organizing, actuating and controlling (POAC).